2007
DOI: 10.1136/bjo.2007.119198
|View full text |Cite
|
Sign up to set email alerts
|

Two strategies for correcting refractive errors in school students in Tanzania: randomised comparison, with implications for screening programmes

Abstract: The low prevalence of un/undercorrected RE and poor uptake of spectacles, even when provided free, raises doubts about the value of vision-screening programmes in Tanzanian secondary schools. Policy decisions on school vision screening in middle- and low-income countries should take account of the cost-effectiveness as well as competing demands for scarce resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
5
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 16 publications
5
94
5
2
Order By: Relevance
“…free glasses 3,6,7 and educational interventions to promote spectacle wear 3,12 have generally shown low uptake, the current report demonstrated that free glasses combined with education on their use and a teacher incentive maintained wear in between two-thirds and 90% of children needing them over the course of a school year. The impact of the intervention on spectacle wear at 6 months was greater than that of family wealth, parental spectacle wear, and children's uncorrected VA. Our main study outcome, observed wear at the time of an unannounced examination, might be expected to underestimate true daily use of spectacles somewhat.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 58%
See 3 more Smart Citations
“…free glasses 3,6,7 and educational interventions to promote spectacle wear 3,12 have generally shown low uptake, the current report demonstrated that free glasses combined with education on their use and a teacher incentive maintained wear in between two-thirds and 90% of children needing them over the course of a school year. The impact of the intervention on spectacle wear at 6 months was greater than that of family wealth, parental spectacle wear, and children's uncorrected VA. Our main study outcome, observed wear at the time of an unannounced examination, might be expected to underestimate true daily use of spectacles somewhat.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 58%
“…3,6,7,[23][24][25] Observed rates of wear were low, ranging from 13% to 41%. 3,6,7,21,23,24 All of the few studies reporting higher rates (46% by Keay and associates in China, 25 56% by Vincent and associates in Thai refugee camps, 22 and 58% by von-Bischhoffshaussen and associates in Chile 20 ) relied on self-report and/or estimates of teachers or parents, 20,22 and had low (58%-76%) rates of follow-up 20,22 or assessment times as short as 1 month after spectacle distribution. 25 It would appear that longer-term (over the course of a school year) compliance with free spectacles, as measured by objective indicators such as observed wear at unannounced examinations, is low among children without additional interventions.…”
Section: Whereas Previous Studies Of Programs Providingmentioning
confidence: 99%
See 2 more Smart Citations
“…As many as 13 million worldwide, have uncorrected refractive error, numerous programs have attempted to address the problem of uncorrected refractive error through school-based vision testing and spectacle distribution programs. Unfortunately, most programs have found that at follow up, the majority of children provided spectacles at no charge were not wearing them or non compliant on wearing refractive correction (5,7,(13)(14)(15)21) Reasons for non-compliance vary by study and population, most common reasons were lost or broken eyeglasses, concern about appearance or teasing, worry that the eyeglasses will make the eyes worse, eyeglasses kept at home or used only for special occasions (1-7, 16, 21) .…”
Section: Introductionmentioning
confidence: 99%